2021
DOI: 10.15376/biores.16.3.5766-5779
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic welding of folding boxboards

Abstract: Today’s environmental concerns are pressuring industries to substitute paper-based materials in place of plastics in many sectors including packaging. However, assembling papers and paperboards using environmentally friendly solutions remains a technological challenge. In this context, ultrasonic (US) welding is an alternative to adhesives. In this work, the potential of US welding to assemble folding boxboards was investigated. Folding boxboards are commonly coated to enhance printability. This coating is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In this context, the main concern of the present study is to investigate on the ultrasonic (US) welding as a potential processing method to assemble papers coated with PVOH and grafted by chromatogeny. US welding has recently emerged as a possible solution to manufacture bio-based materials (Regazzi et al 2019a;Teil et al 2021) and to assemble papers and paperboards (Regazzi et al 2019b;Monot et al 2021;Charlier et al 2021). US welding is a processing method which consist in applying high-frequency acoustic vibrations (20 to 40 kHz) under pressure (Tolunay et al 1983;Benatar et al 1989).…”
Section: Fig 1: Principle Of the Chromatogeny Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the main concern of the present study is to investigate on the ultrasonic (US) welding as a potential processing method to assemble papers coated with PVOH and grafted by chromatogeny. US welding has recently emerged as a possible solution to manufacture bio-based materials (Regazzi et al 2019a;Teil et al 2021) and to assemble papers and paperboards (Regazzi et al 2019b;Monot et al 2021;Charlier et al 2021). US welding is a processing method which consist in applying high-frequency acoustic vibrations (20 to 40 kHz) under pressure (Tolunay et al 1983;Benatar et al 1989).…”
Section: Fig 1: Principle Of the Chromatogeny Reactionmentioning
confidence: 99%
“…More recently, Teil et al and Regazzi et al manufactured and characterized biocomposites made of native starch granules and wood fibers and obtained by ultrasonic compression molding (Regazzi et al 2019a;Teil et al 2021). Only a few recent studies, done by the same team of authors, discuss the use US welding to assemble paper-like materials (Regazzi et al 2019b;Monot et al 2021;Charlier et al 2021). While working with 100% lignocellulosic papers, Regazzi et al showed that papers can be welded only for high lignin and hemicelluloses contents in the paper pulp (Regazzi et al 2019b).…”
Section: Fig 1: Principle Of the Chromatogeny Reactionmentioning
confidence: 99%
See 1 more Smart Citation